Pengaruh model pembelajaran kooperatif tipe snowball throwing terhadap motivasi belajar siswa pada mata pelajaran fiqih - Wildani, Anggi Kusumah; Nahriyah, Syafaatun; Syhabudin, Abu; Jamaludin, Gilang Maulana (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
This research is based on the problem of student learning motivation, especially in fiqh subjects at school. This study aims to determine the effect of the application of the snowball throwing type cooperative learning model on the learning motivation of grade IX students in fiqh subjects. This type of research is quantitative research with descriptive and verifiable methods. The population in this study is all grade IX students at MTs Negeri 2 Sumedang. The sample was taken from the entire population, which was 56 students. The results of the study concluded that the average value of the snowball throwing type cooperative learning model variable of 4.02 and the student learning motivation variable of 4.11 were both in the good category. The results of data processing showed that the snowball throwing type cooperative learning model had a large and significant positive influence on students' learning motivation. This is evidenced by the figure obtained R = 0.725 with a determination coefficient of 52.5% and the remaining 47.5% influenced by other factors. Then for the hypothesis test, the results of the ttable > calculation were obtained, namely 7,731 > 2,005, therefore it means that H1 is accepted and H0 is rejected, namely there is an influence of the application of the snowball throwing type cooperative learning model on students' learning motivation.